NILAI-NILAI PENDIDIKAN ADVERSITY QUOTIENT PADA CERITA NABI MÛSÂ DALAM ALQURAN - Muh. Haris Zubaidillah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2017)
The challenge for education that can not be denied is globalization and technological progress on the one hand. On the other hand education is also faced with the increasing variety of life pressures. Paul G. Stoltz invented a new type of intelligence theory from the psychological paradigm, namely Adversity Quotient (ability to face difficulties), that is, a person's ability to observe difficulties and cultivate those difficulties with his or her intelligence so that it becomes a challenge to be solved. The Qur'an is a holy book filled with educational values. Among the content of the Qur'an are stories. One of the stories in the Qur'an is the story of Prophet Moses that is found in many surahs in the Qur'an. In the story of Prophet Moses there are many extraordinary values and lessons especially in how to deal with adversity. From the results of research, revealed the following important matters. The Adversity Quotient's educational value scontained in the story of Prophet Musa in the Qur'an are the values of patience, the value of optimism and unyielding, the value of the great soul and the value of jihad.